Diagnóstico da Anemia Infecciosa Equina em equinos, asininos e muares utilizando peptídelo sintético pgp45 - João Helder Frederico de Faria Naves (2015)
The control of equine infectious anemia (EIA), a disease caused by a lentivírus, is made primarily by the elimination of positive animals detected by the agar gel immunodiffusion test (AGIDT), which is the official test and the only method used for the diagnosis of EIA in Brazil. The AGIDT may show false negative or doubtful results, since a very weak line of precipitation is formed, especially when it comes to newly infected animals or samples from donkeys and mules. In a pioneering study, we mapped and identified by spot synthesis technique an epitope consensus for identify equids infected with EIAV, located in the region encoding the envelope protein gp45 of EIAV. Based on these results, we synthesized a soluble peptide (pgp45) with 20 amino acids in length that was used as antigen in an indirect ELISA test. When evaluated on field, in which 859 equine serum samples were tested it revealed a correlation of 96.1% with AGID and 98.6 and 95.6%, of sensitivity and specificity respectively. The pgp45 was able to detect an animal as seropositive at 13° day after experimental inoculation with the Wyoming strain of EIAV. The peptide pgp45 was efficient in detecting antibodies against EIA in horses, donkeys and mules infected with EIAV as well and, could be an alternative for the diagnosis, especially if used as a screening test, since it has a high sensitivity, contributing to the control of the EIA.